Peran Otoritas Jasa Keuangan Dalam Tindak Pidana Pasar Modal - Arisandi, Juanda (Yayasan Tri Edukasi Ilmiah, 2025)
The capital market has a strategic role in national economic development as a source of financing for the business world and a means of investment for the community. However, the dynamics of the capital market cannot be separated from the potential for criminal acts such as market manipulation, fraud, and insider trading that can harm investors and disrupt the stability of the financial sector. This study aims to analyze the role and authority of the Financial Services Authority in prosecuting capital market crimes, especially after the enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector. This study uses a normative legal method with a statutory and conceptual approach. The results of the study show that the Financial Services Authority has exclusive authority in regulating, supervising, investigating, and enforcing criminal and administrative law against violations in the capital market. This authority is strengthened through the provisions of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector, which provides broader legitimacy to the Financial Services Authority in the context of protecting investors and enforcing market integrity. In addition, the Financial Services Authority applies a proportional penal and non-penal approach as part of a responsive criminal law policy that is oriented towards economic justice.